The Impact of Consumer Negative Online Reviews and The Role of Religiosity on Post-Purchase Behavior of Muslim Consumers: As an Experimental Design - Pratama, Roro Arinda Reswanti Julian; Permana, Rezi M. Taufik; Hamidah, Syifa Fauziah (Almana : Jurnal Manajemen dan Bisnis, 2025)
Online reviews are now a part of consumer preferences in determining product choices. This study aims to investigate the impact of negative online reviews from consumers and the role of religiosity on Muslim consumers' post-purchase behavior. Researchers use experimental designs to test hypotheses. The research focus is on understanding how Muslim consumers respond to negative online reviews as well as how religious factors may influence their responses to post-purchase behavior. This research is expected to provide insight for business practitioners in designing more effective review management and marketing strategies for the Muslim market, as well as providing a theoretical contribution to the understanding of the relationship between consumer reviews, religiosity, and post-purchase behavior.